Captains of the unconscious: Joseph Conrad's portrayal of a true modern self - Koohestanian, Farhang; Omar, Noritah (Elsevier, 2014)
One of the techniques Joseph Conrad employs in his art of storytelling is juxtaposition. Through comparing and contrasting his protagonists and central characters in different novels and novellas, Conrad portrays flaws and deficiencies of his contemporary human attitude to modernity and modern life leading to some of the greatest tragedies in history. Indeed, Conrad is very methodical in exploring human psyche, and his approach bears resemblance to Carl Gustav Jung's psychological propositions. It is not sheer coincidence that of all Conrad's protagonists, it is mainly the captains that survive and prosper. It concludes that Conrad's captains symbolize and represent an ideal role model for those who wishes to individuate and find their true self.